Asparaginase induces apoptosis and cytoprotective autophagy in chronic myeloid leukemia cells - Ping Song; Li Ye; Jiajun Fan; Yubin Li; Xian Zeng; Ziyu Wang; Shaofei Wang; Guoping Zhang; Ping Yang; Zhonglian Cao; Dianwen Ju (2015)
// Ping Song 1, * , Li Ye 1, * , Jiajun Fan 1 , Yubin Li 1 , Xian Zeng 1 , Ziyu Wang 1 , Shaofei Wang 1 , Guoping Zhang 2 , Ping Yang 3 , Zhonglian Cao 3 , Dianwen Ju 1 1 Department of Biosynthesis & The Key Laboratory of Smart Drug Delivery, Ministry of Education, School of Pharmacy, Fudan University, Shanghai, 201203, P.R. China 2 Institute of Biomedical Science, Fudan University, Shanghai, 200032, P.R. China 3 Instrumental Analysis Center, School of Pharmacy, Fudan University, Shanghai, 201203, P.R. China * These authors have contributed equally to this work Correspondence to: Dianwen Ju, e-mail: dianwenju@fudan.edu.cn Keywords: asparaginase, autophagy, apoptosis, chronic myeloid leukemia Received: July 26, 2014      Accepted: December 07, 2014      Published: January 08, 2015 ABSTRACT The antitumor enzyme asparaginase, which targets essential amino acid L-asparagine and catalyzes it to L-aspartic acid and ammonia, has been used for years in the treatment of acute lymphoblastic leukemia (ALL), subtypes of myeloid leukemia and T-cell lymphomas, whereas the anti-chronic myeloid leukemia (CML) effect of asparaginase and its underlying mechanism has not been completely elucidated. We have shown here that asparaginase induced significant growth inhibition and apoptosis in K562 and KU812 cells. Apart from induction of apoptosis, we reported for the first time that asparaginase induced autophagic response in K562 and KU812 cells as evidenced by the formation of autophagosome, microtubule-associated protein light chain 3 (LC3)-positive autophagy-like vacuoles, and the upregulation of LC3-II. Further study suggested that the Akt/mTOR (mammalian target of rapamycin) and Erk (extracellular signal-regulated kinase) signaling pathway were involved in asparaginase-induced autophagy in K562 cells. Moreover, blocking autophagy using pharmacological inhibitors LY294002, chloroquine (CQ) and quinacrine (QN) enhanced asparaginase-induced cell death and apoptosis, indicating the cytoprotective role of autophagy in asparaginase-treated K562 and KU812 cells. Together, these findings provide a rationale that combination of asparaginase anticancer activity and autophagic inhibition might be a promising new therapeutic strategy for CML.